Students’ Perception on Regular English Classes and Advanced English Classes - Anugrahani, Gracia Dea; Arianti, Theresia (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
English classes are currently developing. There are several classifications of English classes, for example Regular English Classes and Advanced English Classes. This research aimed to identify the differences between these classes, as well as find out students' perceptions about these classes. This study took 10 grade 11 students at SMAN 85 Jakarta as participants. This study used document observation sheet and interview questions as research instruments. The results show that in the Regular English Class, it is aimed to have more varied activities compared to the Advanced English Class. This is in line with the Regular English Class learning hours which are longer than the Advanced English Class. However, the implementation (seen in the Learning Activities part in the module) shows the Advanced English Class has more activities. This makes students prefer Advanced English Classes to Regular English Classes.